Proposals of European citizens for reviving the future of shrinking areas - Besana, Flavio (Quaestiones Geographicae, 2021)
Shrinkage, depopulation and the related structural decline threaten development trajectories of more than a quarter of European territories from the present until 2050. In April 2021, the European Commission has launched the Conference on the Future of Europe to involve citizens and players beyond the traditional actors in shaping future policy agendas. The initiative consists of a wide-scale citizen engagement policy offering them a digital framework to actively contribute to the most relevant debates from April to December 2021. Given that shrinkage is a neglected theme in traditional policy arenas, this article examines the proposals of European citizens for reviving the future of shrinking areas. Through content analysis, the article highlights a limited relative presence of shrinkage in the Conference debate. Nevertheless, the results offer insights into the thematic concentration and the affinity of shrinkage with the most popular policy debates. The article also discusses the content of citizens’ ideas for the future of shrinking areas, thus offering concrete proposals that may fuel the definition of future policy agendas.